Analysis of the Impact of MSMEs, Wage Levels, Population Size, and Education Levels on Unemployment in East Java Province - Marisa Kurniawati; Muhammad Arif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Unemployment remains a significant socioeconomic concern, diminishing both productivity and income while potentially triggering broader societal issues. This study investigates how Micro, Small, and Medium Enterprises (MSMEs), wage levels, population size, and education levels affect unemployment rates across districts and cities in East Java Province from 2019 to 2023. Utilizing secondary data sourced from the Central Bureau of Statistics (BPS), this research applies panel data analysis, integrating time series data from 2019 to 2023 with cross-sectional data from 39 districts and cities. Three regression models Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) were examined, with the Fixed Effect Model (FEM) determined as the most suitable approach. Findings reveal that the independent variables collectively influence unemployment rates, as evidenced by an F-statistic of 10.87244 and a p-value of 0.000000, signifying strong statistical relevance. Further analysis reveals that wage levels negatively affect unemployment, implying that higher wages reduce unemployment rates. Meanwhile, population size and education levels positively influence unemployment, suggesting that an increasing population and higher education levels do not necessarily lead to lower unemployment. Interestingly, the study finds that MSMEs do not significantly impact unemployment rates in East Java.